The practical application of a method of analysing the variability of within-step accelerations collected via athlete tracking devices - Buttfield, A.; Ball, K. (Journal of Sports Sciences, 2020)
Resolving intra-stride accelerations from training and game data routinely collected by athlete tracking devices is rarely attempted, even though these data can provide important insights into the physical condition of athletes. This study describes in detail a novel analysis tool which uses accelerometer-based measures of step variability to assess longitudinal consistency of stride technique. The performance of the analysis tool was examined by combining results from the analysis of data collected over the course of an Australian Football League season with instances of missed or modified training. Results demonstrated increased gait-related trunk acceleration variability when training was modified due to load or accumulated game and training activity (p = 0.02) and reduced trunk acceleration variability in the week following a training modification due to any injury described as "ankle", "heel", or any other description that would loosely refer to a joint or bone in the leg (p = 0.01). These results support the findings of recent research which used a slightly modified version of the same analysis tool to demonstrate an increase in gait-related trunk acceleration variability with the increased acute physical load.